Content and format preferences of a depression prevention program: A study in perinatal women - Osma, Jorge; Suso-Ribera, Carlos; Martínez-Borba, Verónica; Barrera, Alinne Z (Anales de Psicología / Annals of Psychology, 2020)
Background: this study investigated ethnic differences in the preferred content and delivery method of a depression prevention program for perinatal women. Method: participants were 163 pregnant (66.9%) and postpartum (33.1%) women. Women identified themselves as Latinas (45.4%) or non-Latinas (54.6%). Results: overall, women preferred individual and onsite therapy across contents. Only when the content was related to improving communication, they were willing to incorporate the partner. There were no ethnic differences in the preferred format. Regarding content, women preferred to receive “information on the pregnancy process including physical and psychological changes.” Non-Latinas had a higher preference for “receiving regular check-ins on their emotional state” than Latinas. Conclusions: these results should be considered when developing future perinatal depression prevention programs and evidence that work needs to be done if we want online interventions to be viewed more favorably by perinatal women.